The investigation of jujube fruit added into diets on performance and meat quality of broiler chickens - Arslan, S; Çiftçi, M (Journal of the Hellenic Veterinary Medical Society, 2025)
This study was conducted to determine the effects of jujube (Ziziphus jujuba Mill.) fruit added at different rates into the mixed feed on performance, carcass characteristics and meat quality of broiler chickens. A total of 160 male broiler chickens (Ross-308) including 40 in each group, were used in the study. The groups were divided into 4 subgroups, including 10 broiler chickens in each. The study groups were set as follows; the group without jujube fruit was the control group, the group with 0.5% jujube fruit was the H-0.5% group, the group with 1% jujube fruit was the H-1 group and the group with 2% jujube fruit was the H-2 group. At the end of the experiment (42nd day), the highest body weight (P<0.01), daily body weight gain (P<0.05), daily feed intake (P<0.01), and feed conversion ratio (P<0.05) were determined in the H-1 group. The highest thigh and heart weights were determined in the H-1 group, while the lowest hot carcass, breast, back-neck weights and carcass yield were determined in the H-2 group (P<0.05). The lowest poly unsaturated fatty acid, omega-6 and omega-3 levels and the highest omega-6/omega-3 ratio were determined in the control group (P<0.05). In the study, mortality rate was similar in all groups (P>0.05). As a result, it was concluded that jujube fruit, which is mainly used for its antioxidant properties, can be used in poultry compound feeds especially at 1% level due to its positive effects on performance, carcass, and meat quality.